Export Model of Four or More Wheeled Vehicles in Indonesia - Emilia, Emilia; Achmad, Erni; H. Prihanto, Purwaka; Mustika, Candra (Universitas Negeri Semarang, 2022)
In the case of Indonesia, manufacturers from abroad have collaborated with Indonesia by buil di ng t hei r own factories so that this is expected to help economic development in the country , but this doesn’t happen in 2020. In the contrary, since the Pandemic of Covid-19, the automotive industry, one of whi ch i s four -wheeled vehicles or cars, experienced a significant decline in exports. Therefore, the purpose of this research is to find out and analyze how the ratio of exports of four or more wheeled vehicles from Indonesia to the main destination countries, especially in the Southeast Asia region and t o di scover and analyze the effect of the exchange rate, population and gross domestic product on the Indonesian export s of four or more wheeled vehicles to main destination countries, especially in the Southeast Asian region. The methods used in this study are descriptive analysis using export ratio and quantitative analysi s using panel data regression. The results showed that based on the ratio of exports of four or more wheeled vehicles from Indonesia to the four main destination countries in Southeast Asi a, t he l argest was t he Philippines with an average of 0.25, followed by Thailand with an average of 0.11 followed by V iet nam with an average of 0.25. an average of 0.049 and finally Malaysia, which is an average of 0.041. The regression results show that the population and exchange rate variables have a significant positive effect while GDP has no significant effect on Indonesia's exports of four or more wheeled vehicles to the four main destination countries in Southeast Asia.